ANALISIS KOMPOSISI DAN POTENSI HUTAN PRODUKSI DI WILAYAH KESATUAN PENGELOLAAN HUTAN (KPH) DAMPELAS TINOMBO KECAMATAN DAMPELAS KABUPATEN DONGGALA - Taati, La (Katalogis, 2015)
Forest as a gift and the mandate of Almighty God bestowed upon the people of Indonesia is a priceless natural wealth; therefore, it must be grateful. His gift is a mandate, therefore, forests must be managed and utilized wisely as a manifestation of gratitude to Allah SWT. Production forest in the KPH areas DampelasTinombo which is in ParisanAgung Village, Dampelas Sub-District indicates that about 410 hectares are in damage, therefore,Â  it is needed a study about the composition and the potential production forest in Parisanvillage forplanning utilization and plantation forest development which aims at providing welfare for the people who live around the forest area without changing its main function. This research was conducted for 3 months starting from September to November 2015. This research is located at production forest area in the territory of KPHDampelasTinombo which is still territory of ParisanAgung village, Dampelas Sub-district, Donggala, Central Sulawesi. The composition of productional vegetation forest in ParisanAgung Village are 28 vegetation types. The tree level vegetation in the plot is 165 individuals of 25 species of vegetation, the poles vegetation is 140 individuals of 25 species of vegetation, sapling level is 146 individuals of 28 species of vegetation and seedling is 154 individuals of 28 species of vegetation. The potential volume of trees that were in observation plot is 162.53 m3 of 165 individuals, mompi species have the highest volume with 13.17 m3 and the volume level of the pole inside the observation plot is 17.89 m3 of 140 individuals, perupuk kind has the highest volume with 1.63 m3.